Targeting bladder urothelial carcinoma with pHLIP-ICG and inhibition of urothelial cancer cell proliferation by pHLIP-amanitin - Moshnikova, Anna; Golijanin, Borivoj; Amin, Ali; Doyle, Joshua; Kott, Ohad; Gershman, Boris; DuPont, Michael; Li, Yujing; Lu, Xiongbin; Engelman, Donald M.; Andreev, Oleg A.; Reshetnyak, Yana K.; et al. (Frontiers in Urology, 2022)
Acidity is a useful biomarker for the targeting of metabolically active cells in tumors. pH Low Insertion Peptides (pHLIPs) sense the pH at the surfaces of tumor cells and can facilitate intracellular delivery of cell-permeable and cell-impermeable cargo molecules. In this study we have shown the targeting of malignant lesions in human bladders by fluorescent pHLIP agents, intracellular delivery of amanitin toxin by pHLIP for the inhibition of urothelial cancer cell proliferation, and enhanced potency of pHLIP-amanitin for cancer cells with 17p loss, a mutation frequently present in urothelial cancers. Twenty-eight ex-vivo bladder specimens, from patients undergoing robotic assisted laparoscopic radical cystectomy for bladder cancer, were treated via intravesical incubation for 15-60 minutes with pHLIP conjugated to indocyanine green (ICG) or IR-800 near infrared fluorescent (NIRF) dyes at concentrations of 4-8 M. White light cystoscopy identified 47/58 (81%) and NIRF pHLIP cystoscopy identified 57/58 (98.3%) of malignant lesions of different subtypes and stages selected for histopathological processing. pHLIP NIRF imaging improved diagnosis by 17.3% (p < 0.05). All carcinoma-in-situ cases missed by white light cystoscopy were targeted by pHLIP agents and were diagnosed by NIRF imaging. We also investigated the interactions of pHLIP-amanitin with urothelial cancer cells of different grades. pHLIP-amanitin produced concentration- and pH-dependent inhibition of the proliferation of urothelial cancer cells treated for 2 hrs at concentrations up to 4 M. A 3-4x enhanced cytotoxicity of pHLIP-amanitin was observed for cells with a 17p loss after 2 hrs of treatment at pH6. Potentially, pHLIP technology may improve the management of urothelial cancers, including imaging of malignant lesions using pHLIP-ICG for diagnosis and surgery, and the use of pHLIP-amanitin for treatment of superficial bladder cancers via intravesical instillation.